UPAYA MENINGKATKAN KEMAMPUAN MENULIS SISWA DENGAN MODEL PEMBELAJARAN THINK TALK WRITE KELAS V SD NEGERI 118273 MAMPANG KECAMATAN KOTAPINANG KABUPATEN LABUHAN BATU SELATAN - Irda Suriani (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2022)
The inability of students to express their ideas and ideas in written form causes students to think more and remain silent but are less able to write so that students are passive in expressing their creative ideas in writing and are lazy in expressing their brilliant ideas in writing. This reason is the background of this research so that it is hoped that by using a variety of learning models students are better able to develop their writing skills so as to create even better writing skills. The formulation of this research is how to apply the Think Talk Write learning model in improving the writing skills of fifth grade students at SD Negeri 118273 Mampang Village, Kotapinang District, Kbaupaten, Labuhan Batu Selatan. The purpose of this study was to find out how far the application of the Think Talk Write learning model improves writing skills in class V SD Negeri 118273, Mampang Village, Kotapinang District, Kbaupaten, Labuhan Batu Selatan. This research is in the form of Classroom Action Research (CAR) using two cycles with the first stages being planning, action, observation and reflection. The subjects of this study were fifth grade students at SD Negeri 118273 Mampang Village, Kotapinang Kbaupaten District, Labuhan Batu Selatan. The results of the students' writing tests that have been carried out have initial conditions where the average grade in the class is 62.5 with a presentation of 31%. for this test in cycle I obtained an average class 70 presentation of 69%. then for the students' writing ability test cycle II with an average score of 83 with a completeness of 92%. so that it can be concluded that the application of the Think Talk Write model is able to improve the writing skills of fifth grade students at SD Negeri 118273 Mampang Village, Kotapinang District, Labuhan Batu Selatan Regency. Keywords: Writing Ability, Think Talk Write Learning Model.